Adjektiva Kowai dan Osoroshii sebagai Sinonim dalam Bahasa Jepang - Permana, Rixy Gita; Maulana, Rendiansyah Bagus (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2025)
This study examines the synonymous adjectives kowai and osoroshii in Japanese, both of which are often translated into Indonesian as “scary” or “frightening.” Although the two words share a similar meaning, their nuances and contextual uses differ. The aim of this research is to explain the meanings and distinctions between these adjectives through a syntactic-semantic approach, to identify the sentence structures in which they appear, and to address the limitations of previous studies. The data were analyzed using Nitta’s (1997:14, in Sutedi, 2019:61) theory of syntax and Pateda’s (2010:116) theory of contextual meaning. In this study, seven instances of kowai and osoroshii were collected from Japanese-language websites and a Japanese corpus, focusing on subjective and objective contexts across linguistic, extralinguistic, and social aspects. The findings reveal that kowai is more frequently used to express subjective or emotional fear experienced by humans, typically appearing with animate subjects and conveying personal experiences. In contrast, osoroshii refers to external situations or conditions that are objectively dangerous or threatening, and is often used in sentences that describe external conditions or factual states. The choice between the two is strongly influenced by syntactic context and subject–predicate relations in the sentence. Thus, a deep understanding of meaning and syntax is essential for learners of Japanese to use these synonyms appropriately.